The betania reservoir is one of the most important water bodies in colombia, genera - Carrera, Silvia Cristina
The betania reservoir is one of the most important water bodies in colombia,generating energy, fishing activity and economic contribution to the region ofhuila. the objective of the present study was to characterize the differentzooplankton species, bio-indicators of the water quality present in the betaniadam (huila department) between the years 2013-2015. ten sampling points weredetermined by collecting zooplanktonic microorganisms using two methods:depth - depth 1ds and 3ds, followed by the horizontal method and the taxonomyof zooplankton was determined. inferential analyzes of two factors, using thegeneral linear model, repeated measures anova and the kruskal-wallis test as anon-parametric alternative: (p≤0.05). a total of 32 different species ofzooplanktonic microorganisms (individuals/mL) were found, where 55%corresponded to the genus copepod (nine species), 26% to the cladocera genus (8species) and 19% to the genus rotifera, with 15 species of zooplanktonmicroorganisms identified. comparing zooplankton evolution in 1991 in thebetania reservoir where 23 species and 7 families, represented by a species ofcopepod, three species of cladocerans and 19 species of rotifers were found. inthis study (2013-2015) were discovered 32 species, that is to say nine previouslyunobserved species: 11 families (four new), eight species of copepods (sevennew), nine cladoceran species and 15 rotifers. this represented a significantincrease of 39% more species and 57% more families.